The Influence of the Development of Yogyakarta International Airport on the Economy of the People of Temon District, Kulon Progo Regency - Selviya Andri Kusuma; Yunus Purnama (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The construction of Yogyakarta International Airport in Temon District, Kulon Progo Regency has had a significant impact, namely the conversion of agricultural land to the function of agricultural land, the eviction of residential areas and so on. This resulted in socio-economic impacts on the surrounding community and required adaptation to the new economy. The aim of this research is to find out whether there is an influence of the construction of Yogyakarta International Airport on the Community's Economy in Temon District, Kulon Progo Regency on people's perceptions and how much influence it has. This study uses quantitative research methods to examine certain populations or samples. Sampling was carried out by Probability Sampling using the Cluster Sampling method with consideration of indigenous people or living in Temon District with a total of 115 samples. The data used by researchers are primary data with observation and distribution of questionnaires and secondary data. Testing the instrument using validity and reliability, while testing the hypothesis using a simple regression test, partial test (t-test) and test the coefficient of determination. The results showed that the construction of Yogyakarta International Airport had a positive influence on the economy of the people of Temon District, Kulon Progo Regency, as evidenced by the simple linear regression test having positive coefficients and positive constants. Testing on the partial test (t-test) resulted in a value of 0.000 0.5, in the coefficient of determination test it produced a value of 0.607 or 60.7%. The positive influence felt by the community is the increase in the economy both from technological advances and population growth. So the better the construction of the airport will increase the community's economy.